The triple π-bridge strategy for tailoring indeno[2, 1-b]carbazole-based HTMs enables perovskite solar cells with efficiency exceeding 21%. Issue 13 (15th March 2021) - Yao, Huiyun; Wu, Tai; Wu, Bingxue; Zhang, Heng; Wang, Zhihui; Sun, Zhe; Xue, Song; Hua, Yong; Liang, Mao
Abstract : Methoxy-free donors are an emerging class of alternative methoxy triphenylamine materials toward stable organic hole-transporting materials (HTMs). Abstract : Methoxy-free donors are an emerging class of alternative methoxy triphenylamine materials toward stable organic hole-transporting materials (HTMs). However, low cost, stable and efficient methoxy-free donors are scarce. Moreover, the lack of a molecular design strategy limits the further development of methoxy-free donor-based HTMs. This study reports a newly developed low cost hybrid methoxy-free donor ( viz., indeno[2, 1- b ]carbazole) as well as a triple π-bridge strategy to enhance the performance of methoxy-free donor-based HTMs. Based on this strategy, two new indeno[2, 1- b ]carbazole HTMs, termed M136 and M138, were tailor-made and tested in perovskite solar cells (PSCs). Upon incorporating the triple π-bridges ( i.e. thiophene-dithieno[3, 2- b :2′, 3′- d ]pyrrole-thiophene and thiophene-3, 4-ethylenedioxythiophene-thiophene), the resulting indeno[2, 1- b ]carbazole HTMs (M136 and M138 ) exhibit a significantly increased hole mobility, improved charge extraction and minimized trap-assisted recombination as compared to M135 and M137 with unitary and binary bridges, respectively. Consequently, the optimized devices based on M138 achieved an efficiency of 21.37%, which is among the top efficiencies for PSCs based on methoxy-free donor HTMs. The findings demonstrate that indeno[2, 1- b ]carbazole is an excellent methoxy-free donor. In addition, this work underscores the effectiveness of π-bridge engineering to improve the performance of methoxy-free donor-based HTMs.